Energy alternatives in large-scale wastewater treatment - Gabnai, Zoltán (Applied Studies in Agribusiness and Commerce, 2017)
In my article, after describing the characteristics of recent wastewater treatment activity, I introduce different traditional and innovative energetic opportunities of the compulsory waste management activities at large-scale operational level, covering national and international examples. Furthermore, the wastewater-based biomethane production and the certain plant’s energy self-sufficiency are highlighted topics as well. In the former case, it is possible to utilize the wastewater-based biomethane as fuel (and even to operate own vehicle fleet), while the second one gives the opportunity for the internal usage of produced electricity and waste heat, which can also result in significant cost-savings. As an additional option, algae-based wastewater post treatment is presented, based on the conditions of a Hungarian wastewater treatment plant, which biogas production efficiency and thus energy self-sufficiency has developed favourably due to the technological improvements. These plants may have a twofold role in the future: they are responsible for the compulsory waste management activity and on the other hand they can serve as excellent raw material mines.JEL Code: Q25